Proteolysis of Gingival Keratinocyte Cell Surface Proteins by Gingipains Secreted From Porphyromonas gingivalis – Proteomic Insights Into Mechanisms Behind Tissue Damage in the Diseased Gingiva - Hočevar, Katarina; Vizovišek, Matej; Wong, Alicia; Kozieł, Joanna; Fonović, Marko; Potempa, Barbara; Lamont, Richard J.; Potempa, Jan; Turk, Boris (Frontiers in Microbiology, 2020)
Porphyromonas gingivalis, the main etiologic agent of periodontitis, secretes cysteine proteases named gingipains. HRgpA and RgpB gingipains have Arg-specificity, while Kgp gingipain is Lys-specific. Together they can cleave an array of proteins and importantly contribute to the development of periodontitis. In this study we focused on gingipain-exerted proteolysis at the cell surface of human gingival epithelial cells (telomerase immortalized gingival keratinocytes [TIGK]) in order to better understand the molecular mechanisms behind tissue destruction in periodontitis. Using mass spectrometry, we investigated the whole sheddome/degradome of TIGK cell surface proteins by P. gingivalis strains differing in gingipain expression and by purified gingipains, and performed the first global proteomic analysis of gingipain membrane proteolysis. Incubation of TIGK cells with P. gingivalis resulted in massive degradation of proteins already at low multiplicity of infection, whereas incubating cells with purified gingipains resulted in more discrete patterns, indicative of a combination of complete degradation and shedding of membrane proteins. Most of the identified gingipain substrates were molecules involved in adhesion, suggesting that gingipains may cause tissue damage through cleavage of cell contacts, resulting in cell detachment and rounding, and consequently leading to anoikis. However, HRgpA and RgpB gingipains differ in their mechanism of action. While RgpB rapidly degraded the proteins, HRgpA exhibited a much slower proteolysis indicative of ectodomain shedding, as demonstrated for the transferrin receptor protein 1 (TFRC). These results reveal a molecular underpinning to P. gingivalis-induced tissue destruction and enhance our knowledge of the role of P. gingivalis proteases in the pathobiology of periodontitis. Proteomics data are available via ProteomeXchange with identifier PXD015679.